Comparative cross-sectional study regarding the knowledge and attitude of dental students toward biomedical waste legislation, segregation, and management practice - Santosh Mahajan; Harsimran Singh Kapoor; Jagtar Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: Dental practices generate a huge amount of biomedical waste (BMW) and dental waste contaminated with body fluids and many toxic chemicals. Improper handling of these wastes affects the surroundings and health of all living beings of that area. It is, therefore, important for budding dentists to be well versed with the existing rules and regulations of BMW management and the harmful effects of these wastes. Materials and Methods: A cross-sectional questionnaire-based study was carried out among undergraduates, interns, and postgraduate students pursuing dentistry in a dental institute in Punjab. The responses of the student were recorded and analyzed statistically using Chi-square test and Student's t-test. Results: The mean knowledge score of the students about the segregation of BMW is significantly more than legislation (P = 0.003) and management (P = 0.03). The knowledge of preclinical students is found to be less than other students. More than 80% opined that and there should be a regular program on BMW management and it should be made a compulsory part of the college education. Conclusion: Although the knowledge of students attending patients is more than the preclinical students, their overall awareness is less than adequate. It is envisaged through this study that implementing BMW management to be a compulsory part of college education could help to fill the lacuna in the knowledge of the present scenario.